Aspects to Consider in the Evaluation of Photovoltaic System Projects to Avoid Problems in Power Systems and Electric Motors - Charris, Narciso Castro; Santos, Vladimir Sousa; Eras, Juan José Cabello (International Journal of Energy Economics and Policy, 2023)
This paper analyzes the problems in electrical power systems with high penetration of photovoltaic systems, which must be considered in evaluating new projects with these generation sources. The study analyzes the characteristics of photovoltaic systems, their generated effects, and proposals for technological improvements. The features of electric motors and their affectation when they are fed from networks with power quality problems are also described. As a result, the variability in energy production, the difficulties in frequency regulation, the increase in harmonics, and the instability in generating reactive power, are the main problems caused by the massive use of photovoltaic systems. Regarding electric motors, it is shown that harmonics and voltage regulation are the power quality problems that most affect their operation. None of the studies conducted analyzes the direct influence that photovoltaic systems can have on the process of electric motors. Considering the growth prospects for using photovoltaic systems and the importance of electric motors, it is suggested that the scientific community develop research focused on this problem.